Implementation of Low Impact Development (LID) for Urban Drainage Optimization and Flood Mitigation - Amin, Rais; Rinanti, Astri; Kurniyaningrum, Endah; Anggraini, Dina Paramita; Assidik, Muhammad Luthfi (VOCATECH: Vocational Education and Technology Journal, 2025)
AbstractThe frequent problems of flooding and waterlogging in Serang City are triggered by unpredictable rainfall patterns and the limited capacity of the drainage system. The increasing land-use changes and rapid development put additional pressure on the existing drainage channels, leading to excessive runoff and exacerbating the flood risks in several urban areas. This study aims to evaluate the implementation of Low Impact Development (LID) approaches to improve the performance of urban drainage systems in Serang City to reduce water runoff and enhance the capacity of the drainage system to handle the frequent flooding risks. Unpredictable rainfall patterns, combined with the limited capacity of drainage channels, have caused waterlogging and flooding in some areas of the city. Simulations using the Storm Water Management Model (SWMM) software indicate that the implementation of LID techniques, such as bioretention and permeable pavement, is effective in reducing runoff volume flowing into the drainage system and improving water flow efficiency. The simulation results show a reduction in the continuity error value of surface runoff from -0.62% to -0.38%, which is still within an acceptable limit. However, one channel still experiences waterlogging due to limited channel capacity and suboptimal slope. These findings suggest that LID implementation can be a long-term solution to address drainage and flooding issues in urban areas. This study also contributes significantly to designing more environmentally friendly drainage systems, taking into account the impacts of climate change and rapid urbanization. AbstrakMasalah genangan dan banjir yang sering terjadi di Kota Serang, dengan dipicunya perubahan pola curah hujan yang tidak menentu dan kapasitas sistem drainase yang terbatas. Meningkatnya perubahan tata guna lahan dan pembangunan yang pesat menambah tekanan pada saluran drainase yang ada, sehingga menyebabkan terjadinya limpasan air yang berlebihan dan memperburuk risiko banjid ri beberapa kawasan kota. Penelitian ini bertujuan untuk mengevaluasi penerapan pendekatan Low Impact Development (LID) dalam meningkatkan kinerja sistem drainase perkotaan di Kota Serang guna mengurangi limpasan air dan meningkatkan daya tampung sistem drainase terhadap potensi banjir yang sering terjadi. Perubahan pola curah hujan yang tak terduga, ditambah dengan kapasitas saluran drainase yang terbatas, menyebabkan terjadinya genangan dan banjir di beberapa area kota. Simulasi menggunakan perangkat lunak Storm Water Management Model (SWMM) menunjukkan bahwa penerapan LID, seperti bioretensi dan perkerasan berpori, efektif mengurangi volume limpasan yang mengalir ke dalam sistem drainase dan meningkatkan efisiensi aliran air. Hasil simulasi menunjukkan penurunan nilai continuity error pada surface runoff dari -0,62% menjadi -0,38%, yang masih berada di bawah batas yang dapat diterima. Meskipun demikian, terdapat satu saluran yang masih mengalami genangan karena kapasitas saluran terbatas dan kemiringan yang tidak optimal. Temuan ini mengindikasikan bahwa penerapan LID dapat menjadi solusi jangka panjang untuk mengatasi masalah drainase dan banjir di perkotaan. Penelitian ini juga memberikan kontribusi penting dalam merancang sistem drainase yang lebih ramah lingkungan, dengan mempertimbangkan dampak perubahan iklim dan urbanisasi yang cepat.